Front Cover: Cover Image, Volume 21, Issue 5. Issue 5 (29th August 2018) - Davis, Katie; Margolis, Amy E.; Thomas, Lauren; Huo, Zhiyong; Marsh, Rachel
Abstract : The cover image, by Katie Davis et al., is based on the Paper Amygdala sub‐regional functional connectivity predicts anxiety in children with reading disorder, DOI: 10.1111/desc.12631 . Photo Credit: Squid Quinn Photography. Model: Olympia Marxie